2020
DOI: 10.1186/s40729-020-00228-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behavior of three different types of internal tapered connections after cyclic and static loading tests: experimental in vitro

Abstract: Background: In the long-term success of a dental implant, the reliability and stability of the implantabutment interface are important. Studies of maximum force of dental implants with different loading values have been used. This study aims to evaluate the influence of the oblique cyclic loading on the maximum force supported in one-piece and two-piece abutments installed on internal tapered implants. Findings: Sixty implants and sixty prosthetic abutments were divided into six groups (n = 10): G1 and G2 (two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Several studies have tested dental implants using static loading, while others use cyclic loads [32]. Most of the reviews focus on implant design but does not mention fatigue as a complex failure mode [22]. A few studies have considered the effect of the implant diameter on fatigue performance, concluding that narrow implants failed to show typical fatigue behavior, which might be attributed to the implant design [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have tested dental implants using static loading, while others use cyclic loads [32]. Most of the reviews focus on implant design but does not mention fatigue as a complex failure mode [22]. A few studies have considered the effect of the implant diameter on fatigue performance, concluding that narrow implants failed to show typical fatigue behavior, which might be attributed to the implant design [33].…”
Section: Discussionmentioning
confidence: 99%
“…The implant system does not offer long-term integrity of the connection complex, representing a significant risk of fractures [20,21]. Some aspects of the different connection configurations, such as biomechanical resistance and stress distribution, are crucial [22]. Not much is known about implant fatigue detailed by the type of connection.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Sinjari et al in 2019 have shown how even after 10 years of function, this type of connection presented a reduced marginal bone loss compared to internal hexagon, with an extremely low failure rate (in terms of debonding) [ 40 ]. Otherwise, the possibility of having a conometric connection with a screw and an anti-rotational system makes clinical practices easier [ 38 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A static loading test was conducted at a speed of 1.0 mm/min to determine the maximum load [ 17 ]. A flexural load was applied to the implant–abutment assemblies at a rate of 0.5 mm/s [ 18 ]. The bending load acquired by the load cell was plotted on a load versus displacement curve.…”
Section: Methodsmentioning
confidence: 99%